2022
DOI: 10.1039/d2ob01251k
|View full text |Cite
|
Sign up to set email alerts
|

Haber-independent, asymmetric synthesis of the marine alkaloid epi-leptosphaerin from a chitin-derived chiral pool synthon

Abstract: Chitin-derived platforms are emerging as valuable chemical entities for the construction of nitrogenous fine chemicals in processes independent of Haber ammonia. However, much of the work in this area has...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Since practical methods for their preparation have become available in the last decade, 3–6 these building blocks have found several synthetic applications. 7–9…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since practical methods for their preparation have become available in the last decade, 3–6 these building blocks have found several synthetic applications. 7–9…”
Section: Introductionmentioning
confidence: 99%
“…Since practical methods for their preparation have become available in the last decade, [3][4][5][6] these building blocks have found several synthetic applications. [7][8][9] The use of furans in the Diels-Alder (DA) cycloaddition is as old as the named reaction itself. 10,11 The reaction generates a well-defined three-dimensional 7-oxanorbornene structure, with up to four stereocenters, in a single step.…”
Section: Introductionmentioning
confidence: 99%
“…These furans exhibit a rich reactivity profile 22,23 and have been employed in rearrangement reactions, 24,25 cyclo-additions 26,27 and as synthetic building blocks for the preparation of various alkaloids. 28,29…”
Section: Introductionmentioning
confidence: 99%
“…These furans exhibit a rich reactivity profile 22,23 and have been employed in rearrangement reactions, 24,25 cyclo-additions 26,27 and as synthetic building blocks for the preparation of various alkaloids. 28,29 While the formation of an anilide side product was already identified during development of the synthesis of 3A5AF, 19 it was only recently that the first targeted synthesis of anilides from a chitin-derived furan was published by Pastre et al (Scheme 1A). 30 A reduced analogue of 3A5AF, 3-acetamido-5ethylfuran (3A5EF), was used to prepare several substituted anilides via an acetic anhydride mediated Diels-Alder-aromatization sequence under acidic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, we have showcased the utility of 3A5AF in the Haberindependent synthesis of the natural product proximicin A [16], 3-azafurans [17,18], new heteroaromatic scaffolds [19], 2-aminosugars [20] and in a diversity-oriented synthesis (DOS) programme that furnished a number of structurally distinct N-heterocycles [21]. We recently demonstrated that the inherent chirality present in chitin can be transferred to the natural product epi-leptosphaerin A via the chiral pool di-HAF platform [22]. Other research groups have shown that 3A5AF (and derivatives) [23,24] and di-HAF [25] can serve as dienes in the Diels-Alder reaction, while 3A5F has shown significant promise as a platform chemical, including as a bioconjugation handle for N-cysteine's modification [13].…”
Section: Introductionmentioning
confidence: 99%